Carbon limitation overrides acidification in mediating soil microbial activity to nitrogen enrichment in a temperate grassland - Ning, Qiushi; Hättenschwiler, Stephan; Lü, Xiaotao; Kardol, Paul; Zhang, Yunhai; Wei, Cunzheng; Xu, Chengyuan; Huang, Jianhui; Li, Ang; Yang, Junjie; Wang, Jing; Peng, Yang; et al. (Global change biology, 2021)
Higher ecosystem nitrogen (N) inputs resulting from human activities often suppress soil microbial biomass and respiration, thereby altering biogeochemical cycling. Soil acidification and carbon (C) limitation may drive these microbial responses, yet their relative importance remains elusive, which limits our understanding of the longer term effects of increasing N inputs. In a field experiment with continuous N addition at seven different rates from 0 to 50 g N m−2 year−1 over 6 years in a temperate grassland of Inner Mongolia, China, we examined the responses of soil microbial biomass and respiration to changes in soil acidity and C availability by adding lime and/or glucose to soil samples. Soil microbial biomass and respiration did only weakly respond to increasing soil pH, but increased strongly in response to higher C availability with increasing N addition rates. Soil net N immobilization increased in response to glucose addition, and soil microbial biomass increased at higher rates than microbial respiration along the gradient of previous N addition rates, both suggesting increasingly reinforced microbial C limitation with increasing N addition. Our results provide clear evidence for strong N‐induced microbial C limitation, but only little support for soil acidity effects within the initial pH range of 4.73–7.86 covered by our study. Field data support this conclusion by showing reduced plant C allocation belowground in response to N addition, resulting in soil microbial C starvation over the long term. In conclusion, soil microbial biomass and respiration under N addition were strongly dependent on C availability, most likely originating from plant belowground C inputs, and was much less affected by changes in soil pH. Our data help clarify a long‐standing debate about how increasing N input rates affect soil microbial biomass and respiration, and improve the mechanistic understanding of the linkages between ecosystem N enrichment and C cycling. Soil acidification and carbon (C) limitation induced by nitrogen (N) enrichment may suppress microbial activity, yet their relative importance remains elusive. Our experiments in the field and laboratory clearly showed that soil microbial C limitation increased with N addition rates, and played the overriding role in modulating soil microbial activity, while soil acidification was of only limited importance. Microbial C limitation is driven by plant, which allocate less C to belowground with increasing N addition. Our study clarifies a long‐standing debate about the mechanisms of N‐induced suppression of soil microbial activity, allowing better predictions of the ecosystem consequences of N deposition.